The Significance of Mobile Applications Based Learning in Creating Awareness of Occupational Health and Safety - Muhamad Faisal Aulia Nugraha; Roemintoyo Roemintoyo; Djono Djono (Journal of Public Health and Pharmacy)
ntroduction: In this study, "We aim to develop and assess the effectiveness of mobile applications to raise students' awareness about occupational health and safety. This is in response to the low awareness among students in Surakarta, which has the potential to increase the risk of danger and diminish their ability to compete in the workforce. The mobile application's development is intended to address these issues".